Influence of two tapings on the reaction time of the peroneal muscles - Ferreira, A. (2011)
This study aimed to investigate the influence of two different types of tapings on the reaction time of the peroneal muscles, using surface electromyography, in female volleyball athletes with sprain history and indicators of instability. A quasi-experimental study with a sample of 15 athletes was conducted. Adhesive elastic tapings heel-lock and kinesiotape, with peroneus and ligament application, were compared. For data analysis the parametric tests repeated measures ANOVA and T test for paired samples were used. The application of the kinesiotape reduced the reaction time of peroneal muscles significantly while the adhesive elastic band had no significative influence on it.